Recent Advances in Palladium-Catalyzed Bridging C–H Activation by Using Alkenes, Alkynes or Diazo Compounds as Bridging Reagents - Zhang, Fulin; Xin, Luoting; Yu, Yinghua; Liao, Saihu; Huang, Xueliang (Synthesis, 2020)
Transition-metal-catalyzed direct inert C–H bond functionalization has attracted much attention over the past decades. However, because of the high strain energy of the suspected palladacycle generated via C–H bond palladation, direct functionalization of a C–H bond less than a three-bond distance from a catalyst center is highly challenging. In this short review, we summarize the advances on palladium-catalyzed bridging C–H activation, in which an inert proximal C–H bond palladation is promoted by the elementary step of migratory insertion of an alkene, an alkyne or a metal carbene intermediate.1 Introduction2 Palladium-Catalyzed Alkene Bridging C–H Activation2.1 Intramolecular Reactions2.2 Intermolecular Reactions3 Palladium-Catalyzed Alkyne Bridging C–H Activation3.1 Intermolecular Reactions3.2 Intramolecular Reactions4 Palladium-Catalyzed Carbene Bridging C–H Activation5 Conclusion and Outlook
Keywords: palladium catalysis; bridging C–H activation; alkenes; alkynes; diazo compounds; migratory insertion